2011
DOI: 10.1177/0160017611400069
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Propensity Score Matching Evaluation of the Social Impacts of Sugarcane Growing on Municipalities in Brazil

Abstract: The expansion of sugarcane growing in Brazil, spurred particularly by increased demand for ethanol, has triggered the need to evaluate the economic, social, and environmental impacts of this process, both on the country as a whole and on the growing regions. Even though the balance of costs and benefits is positive from an overall standpoint, this may not be so in specific producing regions, due to negative externalities. The objective of this paper is to estimate the effect of growing sugarcane on the human d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Scientific literature suggests that the expansion of Brazil's sugarcane industry has generated net benefits for the population, especially in the generation of employment and income, while acting to mitigate the effects greenhouse gas emissions Toneto-Jr et al, 2008;Hoffmann, 2006;Chagas et al, 2012;Satolo and Bacchi, 2013;Bacchi and Caldarelli, 2015). Since the sector's most evident impacts are felt at the local rather than national level, it is reasonable to expect added insights to come from municipality scale analyses, realizing that results of such analysis may not be consistent with national trends.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…Scientific literature suggests that the expansion of Brazil's sugarcane industry has generated net benefits for the population, especially in the generation of employment and income, while acting to mitigate the effects greenhouse gas emissions Toneto-Jr et al, 2008;Hoffmann, 2006;Chagas et al, 2012;Satolo and Bacchi, 2013;Bacchi and Caldarelli, 2015). Since the sector's most evident impacts are felt at the local rather than national level, it is reasonable to expect added insights to come from municipality scale analyses, realizing that results of such analysis may not be consistent with national trends.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Employing the spatial propensity score matching method, these authors concluded that increased sugarcane cultivation in the evaluated municipalities is not relevant to determining social conditions, either for better or for worse. Their study did not consider the impact of sugarcane related industrial processing units (Chagas et al, 2012). Bacchi and Caldarelli (2015) undertook a panel data analysis to examine externalities arising from the expansion of the sugarcane industry in the state of São Paulo using the Municipality Development FIRJAN Index (IFDM).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Chagas, Toneto, & Azzoni (2012) have done a first step towards this direction by using spatial regression techniques in the course of propensity score estimation. This may help to produce better matches of treated and control groups given the spatial pattern of many regional policy instruments.…”
Section: Treatment Group Control Group and Statistical Estimationmentioning
confidence: 99%